Species richness and identity both determine the biomass of global reef fish communities - Jonathan S. Lefcheck (Nature Portfolio, 2021)
Species identity and richness both contribute biodiversity-ecosystem functioning relationships. Here the authors apply a decomposition approach inspired by the Price equation to a global dataset of reef fish community biomass, finding that increased richness and community compositions favouring large-bodied species enhance biomass.